Design of a washing machine with a screw activator - Trach, M. (Запоріжжя : ТДАТУ, 2025)
Technological equipment for washing and cleaning operations is important in the production process of machine repair. One of the methods of cleaning products is immersion in a washing solution, which involves a complex effect on contamination of physicochemical and mechanical factors. To intensify the cleaning process, activators are used, which can be hydraulic, pneumatic, vibrational and mechanical. In turn, machines equipped with mechanical activators are divided into rotary, screw and blade.
Keywords: washing machine; screw activator; screws machine